Hyperthyroidism and immune thrombocytopenia. Issue 708 (October 1984) - Jacobs, P.; Majoos, F.; Perrotta, A.
Abstract : Hyperthyroidism and immune thrombocytopenia occurred concurrently in five patients; in a sixth, thyrotoxicosis developed after successful treatment of the thrombocytopenia. Correction of the hyperthyroidism was followed by a variable pattern of clinical response. In one case with mild asymptomatic thrombocytopenia spontaneous complete remission occurred. Two patients required adrenocorticosteroids to control severe thrombocytopenic purpura during the period of hyperthyroidism, after which complete remission occurred. Another patient with severe symptomatic thrombocytopenia remains with a partially compensated thrombocytolytic state but is without purpura and off all therapy. A fifth patient required splenectomy for drug-resistant thrombocytopenia and remains critically dependent on immunosuppressive therapy. The sixth patient had a relapse of immune thrombocytopenia with subsequent development of thyrotoxicosis but platelet count spontaneously returned to normal after correction of the hyperthyroidism. Pregnancy in two of these six patients was not associated with recurrence of either hyperthyroidism or thrombocytopenia. Management of symptomatic purpura in adults with co-existent hyperthyroidism may differ from that customarily employed since adrenocorticosteroid therapy may need to be extended until euthyroidism has been established before proceeding to splenectomy. When surgery is necessary, the risk of thyrotoxic storm should be anticipated, and the patient appropriately premedicated.